Phase Ib of Sorafenib in Combination With Everolimus in Patients With Advanced Solid Tumors, Selected on the Basis of Molecular Targets. (27th March 2014) - Toffalorio, Francesca; Spitaleri, Gianluca; Catania, Chiara; Dal Zotto, Laura; Noberasco, Cristina; Delmonte, Angelo; Santarpia, Mariacarmela; Vecchio, Fabio; Brunelli, Veronica; Rampinelli, Cristiano; Barberis, Massimo; Fumagalli, Caterina; et al.
Abstract : Author Summary: Background: Molecular alterations of the PI3K and Ras pathways often occur in human cancer. In this trial, the pharmacokinetics, toxicity, and activity of two drugs inhibiting these pathways—everolimus and sorafenib—were investigated. Methods: Thirteen patients with progressing solid tumors were treated with everolimus and sorafenib, according to a 3+3 scheme. Patients were selected on the basis of immunohistochemical expression of tumor molecular targets, including phospho-AKT, -p70S6K, and -ERK1/2. Results: The daily recommended dose identified was 2.5 mg of everolimus and 600 mg of sorafenib. Dose-limiting toxicities included grade 3 asthenia and hand-foot skin reaction. No grade 4 adverse events were observed. The most frequent grade 3 toxicities were hypophosphatemia (30.8%), alanine aminotransferase level increase, asthenia, and anorexia (14%). No pharmacokinetic interactions were identified between everolimus and sorafenib. Of 12 evaluable patients, we observed 2 partial responses, with greater than 10% shrinkage in an additional 5 patients. Objective responses were observed in one patient with a thymoma and in one patient with a lung adenocarcinoma. Tumor shrinkage that did not qualify as a partial response was seen in an abdominal leiomyosarcoma and in adenoid cystic carcinomas. Conclusion: The combination of everolimus and sorafenib is safe. The tumor activity observed in different tumor types could be the result of the combined action of these drugs as well as the molecular selection of the treated population. Further research is warranted to better investigate drugs simultaneously blocking the PI3K and the Ras pathways and to refine patient selection.